Mosaic ratio quantification of isochromosome 12p in Pallister–Killian syndrome using droplet digital PCR - Fujiki, Katsunori (John Wiley and Sons Inc., 2016)

(untitled) (Mol Genet Genomic Med)
BACKGROUND: Pallister–Killian syndrome (PKS) is a prototypic mosaic aneuploidy syndrome caused by mosaic supernumerary marker isochromosome 12p. Cells possessing the isochromosome 12p rapidly diminish after birth in the peripheral blood, often necessitating a skin biopsy for diagnosis. Therefore, a genomic testing that is capable of detecting low percent mosaic isochromosome 12p is preferred for the diagnosis of PKS. METHODS: The utility of the droplet digital PCR system in quantifying the mosaic ratio of isochromosome 12p in PKS was evaluated. RESULTS: Droplet digital PCR was able to precisely quantify isochromosome 12p mosaic ratio, and copy number measured by droplet digital PCR was correlated well with that of fluorescence in situ hybridization analysis. CONCLUSION: Droplet digital PCR should be considered as an effective tool for both clinical and research analytics to precisely quantify mosaic genomic copy number alterations or mosaic mutations.